The Use Of Enterprise Resource Planning For Effective Warehouse Operations Management In Cocoa Marketing Company (Cmc), Ghana; The Mediating Role Of User Satisfaction - Asante, Vera Ansaa (KNUST, 2023)
A thesis submitted to the department of supply chain information systems, school of business, college of humanities and social sciences, knust in partial fulfilment of the requirements for the degree of master of science in logistics and supply chain management